A comparative study between web service and grid service developments in a MDA framework - Sanz, M; de Castro, V; Marcos, E; Bosque, J (2007)
The application of the MDA approach to the development of service-oriented systems facilitates the system migration over different platforms. The specific features of each platform are reflected in the PSM level of MDA. In this paper a comparison between the development of systems based on Web services and the development of systems based on Grid services is presented. The comparative study is carried out through a case study implemented on both a standard Web Service platform and a Grid platform based on the Globus Toolkit 4 middleware. After the study we conclude that a subdivision of the MDA's PSM level in two layers is needed: an upper layer with the characteristics shared by any service-based platform (a WSDL model and a model of the service code) and a lower layer with all the elements required to deploy the services successfully over the concrete execution platform.